2019
DOI: 10.24243/jmeb/3.4.195
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a custom-made mouthguard in a professional basketball team

Abstract: Introduction: Orofacial trauma related with sports happens both in organized or amateur situations. Taking into consideration the group of sports that are collective and of contact, basketball is undoubtedly a sport with a moderate risk of orofacial trauma. Mouthguards can be a preventive measure to reduce the incidence and severity of orofacial trauma, if they are used during sports practice when indicated. Basketball is a sport with a moderate risk to orofacial trauma and the use of mouthguards is still rare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Instead of being prefabricated, health professionals manufacture these protectors through a personalized mold of an individual mouth, in specialized laboratories [30]. Because of the correct adjustment, the impact resistance and shock absorption are enhanced without compromising the comfort of the athlete [52].…”
Section: Custom-made Mouthguardmentioning
confidence: 99%
“…Instead of being prefabricated, health professionals manufacture these protectors through a personalized mold of an individual mouth, in specialized laboratories [30]. Because of the correct adjustment, the impact resistance and shock absorption are enhanced without compromising the comfort of the athlete [52].…”
Section: Custom-made Mouthguardmentioning
confidence: 99%
“…Nevertheless, according to Australian Dental Association, a minimum thickness of 4 mm is required for the labial flange of a mouthguard. Moreira et al [16] developed studies using a custom-made mouthguard produced by the Erkoform 3D Motion with the Occluform-3 accessory considering two plaques of ethyl vinyl acetate 4 mm and 2 mm thick and found that there were no statically significant differences concerning the retention parameters. On the other hand, Takeda et al [17] and Lunt et al [18] report that higher values of thickness for mouthguards improve the protection because they increase the absorbed energy, but excessive thicknesses impair the athletes' comfort and performance.…”
Section: Introductionmentioning
confidence: 99%